Result of the Threshold Test for Saltiness Perception of 35 People who Participated in the Saltiness Test using Test-Disk at the University Festival (Global Journal of Medical Research, 2020)
Hypertension is one of the causes of many lifestyle-related diseases. In Japan, too, we are raising awareness about dietary salt reduction for hypertensive patients. Therefore, the purpose of this study was to understand the results of the salty cognitive threshold test in a wide range of age. This result can be useful data for future salt reduction instruction. Thirty-five people participated in the saltiness cognition threshold test at the university festival. The participants this time had a wide range of ages from the teens to the eighties. Participants answered that they eat out 2-3 times a week. Also, they said that the seasoning they liketo eat is a little salty. Most participants (88.6%) perceived saltiness below 1.25%. Four participants (one male and three females) recognized saltiness in 5.0%. There was no participant didn't recognize the saltiness of all. In the future, it will be better to conduct a questionnaire survey on dietary habits and compare it with the saltiness cognitive threshold test results.
Keywords: saltiness test; cognition; threshold; test-disk; university festival